Environmental remediation of dye effluents using Gracilaria edulis (Marine red alga) mediated green synthesized Ag₂O nanoparticles: Impacts on soil and water quality - G. Visu; N. Muruganantham; P. Anitha; R. Govindharaju; V. Anusuya (Environmental Nanotechnology, Monitoring & Management, 2026)

Marker-based standardisation and in-vitro biological activity evaluation of Sudarshanam tablet – an important ayurvedic formulation - Veena K Namboodiri; Tom Cherian; Anitha R; Swathi M; Suresh V Nampoothiri (Natural Product Research, 2026)

Trophic interactions and ecosystem status assessment of a tropical reservoir in the Western Ghats of India using Ecopath - Mohammed Meharoof; Vinod Kumar Yadav; G.B. Sreekanth; Arpita Sharma; Thankam Theresa Paul; V Anitha (Total Environment Advances, 2026)

High meiofaunal diversity in the Azores revealed through DNA metabarcoding - Francesca Leasi; Nuno V. Álvaro; Luiz F. Andrade; Thiago Q. Araújo; Víctor Aramayo; Tom Artois; Will M. Ballentine; Franziska S. Bergmeier; Andrea Z. Botelho; Ariane Buckenmeyer; Ana T. Capucho; Irina Cherneva; et al. (Marine Biodiversity, 2026)
To advance understanding of meiofauna, key components of marine benthic ecosystems, an international team conducted a morphology-based taxonomic survey and workshop around São Miguel, the largest Azorean island, in 2019. The survey yielded critical baseline data on meiofaunal diversity and, despite taxonomic challenges that limited identification of certain taxa, laid a solid foundation for further research. To expand these findings, additional samples were analyzed using DNA metabarcoding, a powerful tool that assesses multiple facets of biodiversity, including richness, community composition, and phylogenetic diversity. Metabarcoding identified 480 meiofaunal amplicon sequence variants across 14 phyla, more than doubling the 180 taxa recorded through morphology alone. Of these, 298 (approximately 62%) belonged to phyla targeted during the morphology-based workshop. A comparison between the two approaches, focusing on clades addressed during the workshop, revealed overlapping but expanded patterns of diversity relative to morphology-based taxonomy. This consistency supports the metabarcoding’s ability to uncover meiofaunal diversity and underscores the importance of integrating both methods to achieve a more comprehensive understanding of biodiversity and ecological patterns. As the first metabarcoding study in the Azores, this work establishes a biodiversity baseline for a remote and understudied region, indicating greater benthic diversity than previously recognized. By revealing the complexity of these understudied ecosystems, this research contributes to document and support conservation of biodiversity in the Azores and emphasizes the need for further exploration of meiofaunal communities in isolated oceanic environments.

Land Use Land Cover Change Detection for Fish Culture Area Mapping in the Peechi Reservoir - Mohammed Meharoof; Vinod Kumar Yadav; Arpita Sharma; Shekhar Nath Ojha; V. Anitha; Thankam Theresa Paul (Journal of the Indian Society of Remote Sensing, 2025)

Determining the efficacy of phytoconstituents of Ficus religiosa L. against dermatophytes through invitro and insilico approaches - A. Anitha; P. Ponmurugan; V. Hemamalini; D. Arunkumar (In Silico Pharmacology, 2025)

Transforming waste management: leveraging recycletransformernet for effective recycling strategies - A. Devi; Amirtha Saravanan; R. Reeta; V. P. Anitha (Clean Technologies and Environmental Policy, 2025)

Optimization of nutritional properties of black soldier fly larvae via supplementation using oil cakes, husk, Bran and unhatched eggs: applications for Waste-to-Feed conversion and sustain feed enhancement - D. Saicharan; V. Anitha; G. Anitha; A. Kalaisekhar; Bhojendra Patel (Environment, Development and Sustainability, 2025)

Short-Term Response of Mandous Severe Cyclone on Coastal Water Quality Along Southwestern Bay of Bengal, India - Subhasis Pradhan; P. Senthilkumar; Umakanta Pradhan; Subrat Naik; Rabindra Kumar Sahoo; Anitha Gera; Uma Sankar Panda; Pravakar Mishra; M. V. Ramana Murthy; P. Vipin Babu (Pure and Applied Geophysics, 2025)

From cognition to economic valuation of cultural ecosystem services – An evidence from Parambikulam tiger reserve, Kerala - Divya Soman; V. Anitha; Syam Viswanath; M. Sreeraj (Journal for Nature Conservation, 2025)

Development of reverse transcription recombinase polymerase amplification assay for rapid diagnostics of Peanut mottle virus - B. Parameswari; P. Anbazhagan; A. Rajashree; G. V. Chaitra; Kavi Sidharthan; S. K. Mangrauthia; Faisal Yousuf; K. Anitha; Y. Prasanthi; B. Bhaskar; V. Celia Chalam; G. P. Singh (Physiology and Molecular Biology of Plants, 2025)

Improved photocatalytic degradation of organic pollutants using green synthesized ZnO and Ni@ZnO NPs for environmental applications - N.S. Mohan; S. Bhuvaneswari; R. Anitha; V. Vijayalakshmi (Environmental Nanotechnology, Monitoring & Management, 2024)

Effect of novel combination processing technologies on extraction and quality of rice bran oil - Nikitha Modupalli; Anitha Krisshnan; Sunil C. K.; Chidanand D. V.; Venkatachalapathy Natarajan; Anastasios Koidis; Ashish Rawson (Critical Reviews in Food Science and Nutrition, 2024)

Pixel Reduction of High-Resolution Image Using Principal Component Analysis - Ramachandran Radhakrishnan; Manimegalai Thirunavukkarasu; R. Thandaiah Prabu; G. Ramkumar; S. Saravanakumar; Anitha Gopalan; V. Rama Lahari; B. Anusha; Shaik Hasane Ahammad; Ahmed Nabih Zaki Rashed; Md. Amzad Hossain (Journal of the Indian Society of Remote Sensing, 2024)

Peach (Prunus persica (L.) Batsch) seeds and kernels as potential plant-based functional food ingredients: A review of bioactive compounds and health-promoting activities - Neeraj Kumari; Radha; Manoj Kumar; Sunil Puri; Baohong Zhang; Nadeem Rais; Ashok Pundir; Deepak Chandran; Priya Raman; Sangram Dhumal; Abhijit Dey; Marisennayya Senapathy; et al. (Food Bioscience, 2023)

A Simplified Isothermal Recombinase Polymerase Amplification Assay for Detection of Sugarcane bacilliform virus Infection - B. Parameswari; S. K. Sharma; L. Karthikaiselvi; Baby Wangkhem; K. Nithya; R. Viswanathan; G. P. Rao; V. Celia Chalam; K. Anitha (Sugar Tech, 2023)

A novel QTL linked to asparagine synthetase gene for stem height increment in oil palm (E. guineensis Jacq.) identified and validated through integrated genomic approaches - B. Kalyana Babu; R. K. Mathur; G. Ravichandran; P. Anitha; H. P. Bhagya; M. V. B. Venu (Euphytica, 2023)

Coupled physical-biogeochemical simulations of upwelling, ecological response to fresh water - Anitha Gera; R Gayathri; P Ezhilarasan; V Ranga Rao; M V Ramana Murthy (Ecological Modelling, 2023)

Genetic mapping of drought tolerance traits phenotyped under varying drought stress environments in peanut (Arachis hypogaea L.) - Subhasini Ghosh; Supriya S. Mahadevaiah; S. Anjan Gowda; Sunil S. Gangurde; Mangesh P. Jadhav; Anil A. Hake; P. Latha; T. Anitha; V. P. Chimmad; Kiran K. Mirajkar; Vinay Sharma; Manish K. Pandey; et al. (Euphytica, 2022)

First record of Cactus virus X in Dragon Fruit (Hylocereus spp.) in India - B. Parameswari; Bhaskar Bajaru; N. Sivaraj; S. K. Mangrauthia; S. Nagalakshmi; V. K. Baranwal; Prasanna Holajjer; M. Srinivas; K. Anitha (Indian Phytopathology, 2022)

Influence of salinity on the meiofaunal distribution in a hypersaline lake along the southeast coast of India - Pandiya rajan R S; Anitha Gera; Ramu K; Ranga Rao V; Ramanamurthy MV (Environmental Monitoring and Assessment, 2022)

First report on the association of ‘Candidatus Phytoplasma asteris’ with lethal wilt disease of coconut (Cocos nucifera L.) in India - Merin Babu; S. Thangeswari; A. Josephrajkumar; V. Krishnakumar; A. Karthikeyan; V. Selvamani; Mol Daliya; Vinayaka Hegde; H. P. Maheswarappa; Anitha Karun (Journal of General Plant Pathology, 2021)

Multi-class diagnosis of Alzheimer’s disease using cascaded three dimensional-convolutional neural network - Manu Raju; Varun P. Gopi; V. S. Anitha; Khan A. Wahid (Physical and Engineering Sciences in Medicine, 2020)

Antidiabetic, lipid lowering and antioxidant potentiating effect of Canavalia species in high fat diet-streptozotocin induced model - K. Anitha; S. Mohana Lakshmi; S. V. Satyanarayana (Advances in Traditional Medicine, 2020)

Automated segmentation of optic disc using statistical region merging and morphological operations - K. S. Nija; C. P. Anupama; Varun P. Gopi; V. S. Anitha (Physical and Engineering Sciences in Medicine, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Statistical classification of streamflow based on flow variability in west flowing rivers of Kerala, India - T. K. Drissia; V. Jothiprakash; A. B. Anitha (Theoretical and Applied Climatology, 2019)

Evaluation of Circulating Plasma VEGF-A, ET-1 and Magnesium Levels as the Predictive Markers for Proliferative Diabetic Retinopathy - Gopal Niranjan; A. R. Srinivasan; K. Srikanth; Gowda Pruthu; R. Reeta; Ramasamy Ramesh; Rajendiran Anitha; V. Mohana Valli (Indian Journal of Clinical Biochemistry, 2019)

Burden of disease for workers attributable to exposure through inhalation of PPAHs in RSPM from cooking fumes - Anubha Goel; Deepshikha Ola; Anitha V. Veetil (Environmental Science and Pollution Research, 2019)

Flood Frequency Analysis Using L Moments: a Comparison between At-Site and Regional Approach - T. K. Drissia; V. Jothiprakash; A. B. Anitha (Water Resources Management, 2019)

Genetic Diversity Among Indigenous Germplasm of Brassica juncea (L.) Czern and Coss, Using Agro-Morphological and Phenological Traits - Rashmi Yadav; Ranbir Singh; Sandeep Kumar; T. V. Prasad; Rakesh Bharadwaj; Vikender Kaur; Anitha Petapadi; Ashok Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Non-timber forest products certification and management: a socioeconomic study among the Kadars in Kerala, India - Jyotsna Krishnakumar; John F. Yanagida; V. Anitha; Rajeev Balakrishnan; Theodore J. K. Radovich (Environment, Development and Sustainability, 2015)

The multiple associations of Klippel–Feil syndrome - Anitha Jasper; Sniya Valsa Sudhakar; Gibikote V. Sridhar (Acta Neurologica Belgica, 2015)

Shallow geological environment of Krishna–Godavari offshore, eastern continental margin of India as inferred from the interpretation of high resolution sparker data - G ANITHA; M V RAMANA; T RAMPRASAD; P DEWANGAN; M ANURADHA (Journal of Earth System Science, 2014)

Estimation of atmospheric surface layer parameters and numerical simulation using MM5 at Mangalore, West Coast of India - Anitha Kumari Hegde; R. Venkatesan; C. V. Srinivas; K. M. Balakrishna (Meteorology and Atmospheric Physics, 2010)

Changes in structural attributes of plant communities along disturbance gradients in a dry deciduous forest of Western Ghats, India - K. Anitha; Shijo Joseph; E. V. Ramasamy; S. Narendra Prasad (Environmental Monitoring and Assessment, 2009)

Lipoic acid attenuates hypertension and improves insulin sensitivity, kallikrein activity and nitrite levels in high fructose-fed rats - V. Thirunavukkarasu; A. T. Anitha Nandhini; C. V. Anuradha (Journal of Comparative Physiology B, 2004)

Identification of the Sex Pheromone of Holotrichia reynaudi - Andrew Ward; Chris Moore; V. Anitha; John Wightman; D. John Rogers (Journal of Chemical Ecology, 2002)